SAT0315 INHIBITION OF MICROSOMAL PROSTAGLANDIN E SYNTHASE-1 (MPGES-1) BY GS-248 REDUCES PROSTAGLANDIN E2 BIOSYNTHESIS WHILE INCREASING PROSTACYCLIN IN HUMAN SUBJECTS - Edenius, C.; Ekström, G.; Kolmert, J.; Morgenstern, R.; Stenberg, P.; Jakobsson, P. J.; Tornling, G. (Annals of the rheumatic diseases, 2020)
Background:Microsomal prostaglandin E synthase-1 (mPGES-1) catalyzes the formation prostaglandin (PG) E2 from cyclooxygenase derived PGH2(1, 2). Inhibition of mPGES-1 leads to reduction of pro-inflammatory PGE2, while in vessels there is a concomitant increase of vasoprotective prostacyclin (PGI2) via shunting of PGH2(3,4). Apart from relieving symptoms in experimental animal models of inflammation, inhibitors of mPGES-1 cause relaxation of human medium sized arteries(4) and resistance arteries(5). The prostaglandin profile following mPGES-1 inhibition, explains the anti-inflammatory effects and also opens for the possibility of treating inflammatory diseases with concomitant vasculopathies. GS-248 is a potent and selective inhibitor of mPGES-1 exhibiting sub-nanomolar IC50 in human whole blood ex vivo.Objectives:To evaluate safety, tolerability, pharmacokinetics and pharmacodynamics of GS-248.Methods:Healthy males and females (age 18–73 years) were included in the study. Six cohorts were administrated single oral doses of 1-300mg GS-248 (n=36) or placebo (n=12), three cohorts were administered once daily doses of 20-180mg GS-248 (n=18) or placebo (n=12) over ten days. In addition, 8 subjects were treated in a separate cohort with 200mg celecoxib bid for ten days. Blood samples were drawn for measurement of GS-248 exposure and production of PGE2 after LPS incubation ex vivo. The content of PGE2 and PGI2 metabolites was measured in urine. All analyses were performed by LC-MS/MS.Results:GS-248 was safe and well tolerated at all tested dose levels. Maximum plasma concentration was achieved 1 - 2.5 hours after dosing, and half-life was about 10 hours. Induced PGE2 formation ex vivo, catalyzed by mPGES-1, was completely inhibited for 24 hours after a single low dose (40mg) of GS-248. In urine, GS-248 dose-dependently reduced the excretion of PGE2 metabolite by more than 50% whereas the excretion of PGI2 metabolite increased more than twice the baseline levels. In the celecoxib cohort urinary metabolites of both PGE2 and PGI2 were reduced with approx 50%.Conclusion:GS-248 at investigated oral doses was safe and well tolerated. There was a sustained inhibition of LPS induced PGE2 formation in whole blood. In urine, there was a metabolite shift showing reduced PGE2 and increased PGI2, while celecoxib reduced both PGE2 and PGI2 metabolites. This suggests that selective inhibition of mPGES-1 results in systemic shunting of PGH2 to PGI2 formation, leading to anti-inflammatory and vasodilatory effects, while preventing platelet activation. The results warrant further evaluation of GS-248 in inflammatory conditions with vasculopathies such as Digital Ulcers and Raynaud’s Phenomenon in Systemic Sclerosis.References:[1]Korotkova M, Jakobsson PJ. Persisting eicosanoid pathways in rheumatic diseases. Nat Rev Rheumatol. 2014;10:229-41[2]Bergqvist F, Morgenstern R, Jakobsson PJ. A review on mPGES-1 inhibitors: From preclinical studies to clinical applications. Prostaglandins Other Lipid Mediat. 2019;147:106383[3]Kirkby NS, et al. Mechanistic definition of the cardiovascular mPGES-1/COX-2/ADMA axis. Cardiovasc Res. 2020[4]Ozen G, et al. Inhibition of microsomal PGE synthase-1 reduces human vascular tone by increasing PGI2: a safer alternative to COX-2 inhibition. Br J Pharmacol. 2017;174:4087-98[5]Larsson K, et al. Biological characterization of new inhibitors of microsomal PGE synthase-1 in preclinical models of inflammation and vascular tone. Br J Pharmacol. 2019;176:4625-38Disclosure of Interests:Charlotte Edenius Shareholder of: Gesynta Pharma, Consultant of: Gesynta Pharma,, Gunilla Ekström Shareholder of: Gesynta Pharma, Consultant of: Gesynta Pharma,, Johan Kolmert Consultant of: Gesynta Pharma,, Ralf Morgenstern Shareholder of: Gesynta Pharma, Employee of: Gesynta Pharma, Patric Stenberg Shareholder of: Gesynta Pharma, Employee of: Gesynta Pharma, Per-Johan Jakobsson Shareholder of: Gesynta Pharma, Grant/research support from: Gesynta Pharma, AstraZeneca,, Göran Tornling Shareholder of: Gesynta Pharma, Vicore Pharma,, Consultant of: Gesynta Pharma, Vicore Pharma, AnaMar